EP4 Antagonist-Elicited Extracellular Vesicles from Mesenchymal Stem Cells Rescue Cognition/Learning Deficiencies by Restoring Brain Cellular Functions. (19th March 2019) - Chen, Shih-Yin; Lin, Meng-Chieh; Tsai, Jia-Shiuan; He, Pei-Lin; Luo, Wen-Ting; Herschman, Harvey; Li, Hua-Jung
Abstract : Adult brains have limited regenerative capacity. Consequently, both brain damage and neurodegenerative diseases often cause functional impairment for patients. Mesenchymal stem cells (MSCs), one type of adult stem cells, can be isolated from various adult tissues. MSCs have been used in clinical trials to treat human diseases and the therapeutic potentials of the MSC-derived secretome and extracellular vesicles (EVs) have been under investigation. We found that blocking the prostaglandin E2 /prostaglandin E2 receptor 4 (PGE2 /EP4 ) signaling pathway in MSCs with EP4 antagonists increased EV release and promoted the sorting of specific proteins, including anti-inflammatory cytokines and factors that modify astrocyte function, blood–brain barrier integrity, and microglial migration into the damaged hippocampus, into the EVs. Systemic administration of EP4 antagonist-elicited MSC EVs repaired deficiencies of cognition, learning and memory, inhibited reactive astrogliosis, attenuated extensive inflammation, reduced microglial infiltration into the damaged hippocampus, and increased blood–brain barrier integrity when administered to mice following hippocampal damage. Stem Cells Translational Medicine   2019 : Abstract : Brain damage is associated with reactive astrogliosis, extensive inflammation, broken blood–brain barrier, and microglial infiltration into the damaged area. Prostaglandin E2 receptor 4 antagonist-elicited mesenchymal stem cell extracellular vesicles, which are enriched in IL-2, IL-10, vascular endothelial growth factor-a, and BDNF, suppress reactive astrogliosis and inflammation and allow the recovery of CNS neurons, blood–brain barrier, and behavioral function.